Taxonomic study of the Japanese species of the genus Salka Dworakowska (Hemiptera, Cicadellidae, Typhlocybinae) - Ohara, Naomichi (Zootaxa, 2012)
Eight new species of the erythroneurine genus Salka are described and illustrated from the Ryukyu Islands, southern Japan: S.denticulata sp. nov., S. circumflexa sp. nov., S. okinawana sp. nov., S. diversa sp. nov., S. dimorpha sp. nov., S. maesatoensis sp. nov., S. nusukuensis sp. nov. and S. trimaculata sp. nov.